An Exhaustive Analysis of Stress on Faculty Members Engaged in Higher Education - Bist, Ankur Singh; Rawat, Bhupesh; Rahardja, Untung; Aini, Qurotul; Prawiyogi, Anggy Giri (IAIC Transactions on Sustainable Digital Innovation (ITSDI), 2022)
Higher education is the face of innovation for any country. The quality and dedication of professors help to maintain quality in this process. With time, parameters were raised to check the quality of professor attributes. In this paper, we discuss all possible parameters taken by universities to evaluate faculty performance. Gradually it grew overhead pressure on professors and impacted the teaching-learning process. Our paper focused on stress parameters with possible solutions for the same issue. The process consists of several parameters to evaluate an employee's performance, such as no publications in conferences and journals, no patents filed, additional responsibilities performed, other qualifications achieved, result in the analysis of courses taught, etc. Still, it also puts a lot of pressure on both of them because they have to balance all this extra work and teaching. This paper focuses on different faculty assessment parameters and their impact on the faculty teaching-learning process. We also propose possible solutions on how this stress can be alleviated, and the existing strategy can be simplified.